Integrating Concern for Animals into Personal Values. (2nd January 2017) - Dietz, Thomas; Allen, Summer; McCright, Aaron M.
ABSTRACT: Recent scholarship in human–animal relationships demonstrates that new theoretical insights emerge when these relationships are seriously considered. We suggest that the most prominent measures of values in the environmental decision-making research literature, the Schwartz approach, may not adequately capture key aspects of how individuals value animals. Our research used confirmatory factor analysis and ordinary least squares regression techniques on data collected from an Amazon Mechanical Turk online survey. It expands on the values commonly used in the environmental decision-making literature to consider whether there is a distinct value dimension focused on animals. Our suggestion that a "concern for animals" value orientation constitutes a motivation that is separate from the other values commonly used in research on environmental decision-making finds support in our data. Traditional scaling methods indicate that the items we created have high reliability when used to form an unweighted additive scale. The results of confirmatory factor analysis are consistent with the argument that this "concern for animals" value orientation is distinct from biospheric altruism, humanistic altruism, self-interest, traditionalism, openness to change, and hedonism. Finally, our regressions using values and demographic, social, and political characteristics as controls show that an animal-focused value orientation and biospheric altruism have different relationships with identification with the animal rights movement than with identification with the environmental movement.